ENHANCING FIFTH GRADERS’ LEARNING INTEREST THROUGH QR CODE-BASED SNAKES AND LADDERS MEDIA - Dya Ayu Agustiana Putri; Leny Suryaning Astutik (Yayasan Sukma, 2026)
Learning media through games can increase students’ enthusiasm, as reflected in their learning interest. The purpose of this study was to examine the effect of QR Code-based Snakes and Ladders media on the learning interest of fifth-grade students at SD 2 Tiudan in symbiosis material. Specifically, this research aimed to determine whether the integration of QR Code-based interactive elements into traditional Snakes and Ladders could provide a more engaging and effective learning experience, thereby fostering greater student interest in science learning. This research employed a quantitative approach with an experimental design. The sampling technique used saturated sampling with a total of 60 respondents. Data collection was carried out using a learning interest test. Data analysis employed an independent samples t-test using Jamovi 2.3.28. The post-test t-test results showed a p-value < 0.001, which is lower than 0.05, indicating that H0 was rejected and Ha was accepted. Thus, the QR Code-based Snakes and Ladders media significantly influenced the learning interest of fifth-grade students at SD 2 Tiudan in symbiosis material. Based on the hypothesis testing, it was concluded that QR Code-based Snakes and Ladders media had a significant effect on students’ learning interest in the symbiosis topic.